Defensive Architecture and the Depopulation of the Mesa Verde Region, Utah-Colorado in the Thirteenth Century A.D. - Palonka, radoslaw (Prace archeologiczne. Monographs,, 2011)
Thirteenth century A.D. was a time of many changes and reorganization in the ancient Pueblo world in the Mesa Verde region. Still unresolved are the causes of the migration of Pueblo people from the Mesa Verde region to the south and southeast in the end of the century. The theories most cited and most supported by scientific data include environmental changes, increasing conflict and violence, social changes, and the attraction of a new cult or ideologies from the south. However, it seems that none of these theories can fully explain the total depopulation of the region. One reason often cite.